2011
DOI: 10.1007/s11134-011-9254-x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of multi-server polling system with server limits

Abstract: We consider a multi-server polling system with server limits, that is the number of servers that can attend a queue simultaneously is limited. Stability conditions are available when service policies are unlimited. The definition of stability conditions when both server limits and limited service policies apply remains an open problem. We postulate a conjecture for the stability condition in this case that is supported by our simulation results. The study of this particular variant of the multiserver polling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Antunes et al [100] consider a multi-server polling system assuming that the number of servers that can simultaneously visit the same queue is limited. Servers visit the queues independently of each other in a random order.…”
Section: Multi-server Polling Systemsmentioning
confidence: 99%
“…Antunes et al [100] consider a multi-server polling system assuming that the number of servers that can simultaneously visit the same queue is limited. Servers visit the queues independently of each other in a random order.…”
Section: Multi-server Polling Systemsmentioning
confidence: 99%
“…In queueing terms, this gives rise to multiserver polling models, each server representing a wavelength. We refer to [1] for the stability analysis of multiserver polling models, and to [2] for a mean field approximation of large passive optical networks. It would be very interesting to study multiserver polling models with the additional features of retrials and glue periods.…”
Section: Conclusion and Suggestions For Future Researchmentioning
confidence: 99%
“…However, this is unrealistic if the switch-over times are nonzero; then the requirement is weakened: the system's content should merely stay bounded as time progresses [Kumar and Seidman, 1990;Matveev and Savkin, 2000;Lefeber and Rooda, 2006]. Although the main body of the vast literature on polling systems assumes a single server [Takagi, 1997[Takagi, , 2001Vishnevskii and Semenova, 2006], nowadays the "second wave" of interest to the multiple server case is motivated by recent advances in multiple access technologies in passive optical networks [Antunes et al, 2011] and emerging intellectual transportation systems [Boon et al, 2014]. The multiplicity of servers brings strong extra challenges, which make the analysis much more involved and less tractable [Dai, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…By using this result, it is shown that the usual traffic condition ensures positive Harris recurrence of the network under a number of specific standard disciplines. Multiple-server stochastic polling models with individual time-invariant stochastic Markov routing of every server over the buffers are examined in [Fricker and Jaïbi, 1998;Down, 1998;Delcoigne and Fayolle, 1999;Antunes et al, 2011]. In [Fricker and Jaïbi, 1998] necessary and sufficient conditions for stability are established for given service disciplines taken from a specific general class.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation